Class Struggle in Ralph Hosea Chaplin’s Poetry: A Marxist Perspective - Hanifah, Sekar; Santoso, Heri Dwi; Mulyadi, Dodi; Hardiyanti, Diana (SIGEH ELT : Journal of Literature and Linguistics, 2025)
Class struggle emerges due to the gap between two conflicting classes: the bourgeoisie (capital owners) and the proletariat (workers). The oppression and unjust distribution of rights lead the working class to fight for equality. This condition has been immortalized in poetry by poets as a reflection of social realities. This research aims to examine the application of Marxist theory in literature by analyzing class struggle in Ralph Hosea Chaplin’s poems, "The Commonwealth of Toil," "Sabotage," and "Solidarity Forever" (1917). The study employs a qualitative descriptive method using Marxist theory to analyze the representation of power relations and the struggle of the exploited class. The findings reveal that power is in the hands of the bourgeoisie, who exploit and oppress the proletariat without granting their rights. Moreover, the proletariat responds with resistance, starting from ideological awareness to verbal and physical confrontation against the bourgeoisie.